Development and evaluation of a pan‐dermatophyte polymerase chain reaction with species‐level identification using sloppy molecular beacon probes3. (25th February 2019) - Walser, M.; Bosshard, P.P.
Summary: Background: Conventional laboratory diagnosis of dermatophyte infection is cumbersome and time‐consuming. Objectives: We aimed to establish a simple, robust and rapid molecular diagnostic assay for the detection of dermatophytes and optionally nondermatophytes in clinical specimens. Materials and methods: We developed a two‐tube pan‐dermatophyte polymerase chain reaction (PCR) assay using six sloppy molecular beacon (SMB) probes. The first PCR uses dermatophyte‐specific primers and enables detection and identification of most dermatophyte species. The second PCR with pan‐fungal primers allows further differentiation of Trichophyton interdigitale and T. mentagrophytes / T. quinckeanum, T. violaceum and T. soudanense, and T. tonsurans and T. equinum, and detection of nondermatophytes. The test was evaluated with 306 clinical specimens by comparing it with the results of microscopy and culture. Results: In melting‐curve analyses, species‐specific melting temperature signatures of the SMBs were defined, and thus, our new PCR enabled detection and species‐level identification of at least 19 dermatophyte species. Sensitivity and specificity of PCR for detection of dermatophytes in clinical samples were estimated to be 96·9% and 90·4%, for culture 46·7% and 98·7%, and for microscopy 91·4% and 84·0%, respectively. The detection of nondermatophytes by PCR and culture did not correlate. Conclusions: The new assay showed excellent performance characteristics for the detection of dermatophytes and is significantly faster than culturing techniques, which makes it very promising for routine diagnostics of dermatophytosis. We noted that the detection of nondermatophytes in our assay currently has no benefit. Abstract : What's already known about this topic? In recent years, real‐time polymerase chain reaction (RT‐PCR) approaches for direct detection of dermatophytosis have been developed. In RT‐PCR assays, fluorescently labelled oligonucleotide probes are used, which hybridize to species‐specific sequences allowing the simultaneous detection of different species. Thus, usually one to three species are detected in one reaction. What does this study add? The pan‐dermatophyte PCR method developed in this study is highly innovative: in a two‐tube assay with six sloppy molecular beacon probes and melting‐curve analysis, species‐specific melting temperature signatures were defined. The new method enables detection and species‐level identification of at least 19 dermatophyte species directly in clinical specimens. This is the first sealed‐tube PCR assay that allows the detection of all clinically relevant dermatophytes. Linked Comment:  Saunte. Br J Dermatol 2019;180 :1298–1299 . Plain language summary available online Respond to this article